PENGARUH LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MODERASI (Survei pada Karyawan Bodypaint PT Nasmoco Abadi Motor Cabang Ringroad Karanganyar) - Sutarno, Reny Nurmawati, Suprihatmi Sri Wardiningsih & (Universitas Slamet Riyadi, 2017)
This study aimed to analyze the effect of the working environment andcompensation to employee performance. The effect of the working environment andcompensation to employee performance and job satisfaction as a moderating variable.The population in this study were all employees at the BodyPaint PT Nasmoco AbadiMotor Branch Ringroad Karanganyar totaling 40 employees. Data collection techniqueused questionnaire that through stages of testing the validity and reliability. Data wereanalyzed using the validity test, reliability test, classic assumption test, multiple linearregression test, and test-gap absolute value. Based on the survey results revealed thatthe working environment and job satisfaction have a significant effect on employeeperformance. Compensation does not significantly influence employee performance. Jobsatisfaction does not moderate the effect of the working environment and compensationon employee performance of BodyPaint PT Nasmoco Abadi Motor Branch RingroadKaranganyar.Keywords: work environment, compensation, job satisfaction, employee performance